Propaganda and international relations / Urban G. Whitaker, Jr - Whitaker, Urban G. Jr. (1960)
The nature and role of propaganda in internacional relations, history and defenition of propaganda; propaganda agenies of the superpowers, propaganda activities of the superpowers, proposals for government acton on the psychological front, cessaion of nuclear testing a case study in international propaganda.